HUMANINDEX®1: El currículum vítae como fuente de información en la obtención de indicadores científicos en Humanidades y Ciencias Sociales - Gorbea-Portal, Salvador; Cubells-Nonell, Vicente (Revista General de Información y Documentación, 2009)
The authors analyze the possibility of using the curricula vitae of researchers and professors in order to acquire accurate and reliable information that may be regarded as scientific indicators. To this end, diverse indicator types are proposed and structured for understanding the regularities present in each section that make up these documents. The analysis carried out in this way provides the basis for a proposal and subsequent design and implementation of the Sistema Humanindex (Humanindex System), whose aim is to constitute a Standardized Curriculum Vitae that includes a Citation Index showing the researchers’ scientific publications provided in these documents. The paper describes the essential traits and services that the system offers.
Keywords: Scientific Indicators; Citation Index; Curriculum Vitae; Bibliometrics; Humanindex System